The Relationship between Literature, Language and Culture in Ancient Texts: Historical Linguistics - Yaacob, Solehah (Al-Ḍād Journal, 2022)
The aim of this research is to review the relationship between literature, language and culture in terms of ancient texts. The question is not whether the Arabic grammar is a particular grammatical system that has been seized, but the question is, did the Arabs reach the basic linguistic concepts based on the foundations of thinking that they followed by correct data in the form of grammar in the absence of any external influence? As for the Orientalists’ statement that the Arabic language existed after the mission of the Prophet Muhammad, peace and blessings be upon him (pbuh), it is a contradictory statement. Rather, this language existed before the dawn of Islam in the form of dialects used since ancient times in Mesopotamia. These evidences will be of outstanding importance and perhaps a critical contribution to the historical study of the Arabic language and its development. The research discovered some evidence for an exception from being affected by other cultures, including: analogy in the verses of the Noble Qur’an, prose, Arabic poetry and some examples from some translators’ books and inference with some models of the ancient language and its drawings to be evidence that what was developed from the Arabic language and its rules were the innovation of the Arabs and not from others. It follows the historical linguistic analytical method. Keywords: ancient language, grammatical rules, human civilization, literature and its development, acquired culture